2013
DOI: 10.1002/cphc.201201083
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Switching Behavior in Isosteric DNA Base Pairs

Abstract: The structures and proton-coupled behavior of adenine-thymine (A-T) and a modified base pair containing a thymine isostere, adenine-difluorotoluene (A-F), are studied in different solvents by dispersion-corrected density functional theory. The stability of the canonical Watson-Crick base pair and the mismatched pair in various solvents with low and high dielectric constants is analyzed. It is demonstrated that A-F base pairing is favored in solvents with low dielectric constant. The stabilization and conformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 108 publications
0
21
0
Order By: Relevance
“…The NBO package 69 implemented in Gaussian 09 and the standalone AIMALL package (version 11.12.19) 70 were used respectively for NBO and AIM calculations, the relevent parameters for which are described elsewhere. 71,72 The bond paths detected by AIM analysis, associated with a positive slope of the electron density gradient (r 2 r 4 0) at the bond critical point (where rr = 0), were identified as non-covalent interactions. 66 Among them, those which simultaneously satisfy the following criteria were identified as hydrogen bonds, -(i) the range of r values must be between 0.002 a.u.…”
Section: Methodsmentioning
confidence: 99%
“…The NBO package 69 implemented in Gaussian 09 and the standalone AIMALL package (version 11.12.19) 70 were used respectively for NBO and AIM calculations, the relevent parameters for which are described elsewhere. 71,72 The bond paths detected by AIM analysis, associated with a positive slope of the electron density gradient (r 2 r 4 0) at the bond critical point (where rr = 0), were identified as non-covalent interactions. 66 Among them, those which simultaneously satisfy the following criteria were identified as hydrogen bonds, -(i) the range of r values must be between 0.002 a.u.…”
Section: Methodsmentioning
confidence: 99%
“…In order to provide information with regard to the structural characteristics and the normal vibrational modes of Linezolid, the DFT-B3LYP correlation functional calculations were carried out. The experimental molecular geometric data of Linezolid [8] was used for optimization and the entire calculations were performed at ab initio Hartree-Fock (HF) and DFT method using B3LYP/6-31G(d,p), B3LYP/6-311G(d,p) and M06-2X/6-31G(d,p) levels [9][10][11] on a Pentium V/1.6 GHz personal computer using GAUSSIAN 09W software package [12]. The Raman activities (S i ) calculated with the GAUSSIAN 09W program were subsequently converted to relative Raman intensities (I i ) using the following relationship derived from the basic theory of Raman scattering [13,14],…”
Section: Computational Detailsmentioning
confidence: 99%
“…The reliability and stability in the values of AIM parameters have been studied and it was found that they are almost independent of basis set on the use of functional B3LYP in DFT [11]. However, it has been noticed that B3LYP function estimates weak intramolecular interactions as well as charge transfer effects [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…12.36, -12.41, -3.8, -3.53 and − 3.57 kcal/mol, respectively. These data indicate the medium H-bond interactions for N27H39…O25 and N60H72…O58 bonds and other bond are of week interaction[48].…”
mentioning
confidence: 97%